Larangan Penyitaan Aset Lembaga Pengelola Investasi Dalam Undang-Undang Cipta Kerja - Muhammad Aziz Fauzi; Yayuk Whindari (Fakultas Hukum Universitas Islam Malang, 2022)
The conflict of norms that occurred between of Law Number 11 of 2020 concerning Job Creation and Law Number 1 of 2004 concerning the State Treasury and the settlement mechanism. This study uses a normative juridical research method. The results of the study show that there are several indicators that form the basis for the occurrence of norm conflicts. The source of LPI assets is an inseparable part of state property and the laws and regulations that govern it and there is no antecedent that limits state property as assets that are excluded from being subject to confiscation, as well as the payment mechanism with confiscation of state assets contrary to the ratio decidendi of the judge in Constitutional Court Decision Number 25/PUU-VII/2009.